The effect of recreational motor exercises on neuro-motor coordination and 100-meter sprint performance for students - Hussein, L.Samer Salah Abdul; Saad, L.Dr. Mohamed Osman; Hussein, Prof. Dr. Wissam Salah Abdul (Sulaimani Journal for Humanities, 2026)
Researchers specializing in teaching and sports observed that most third-grade students struggled with the 100-meter sprint technique. This study aimed to identify recreational motor exercises that improve neuro-motor coordination and enhance 100-meter sprint skills. The researchers investigated the impact of these recreational exercises on neuro-motor coordination and 100-meter sprint performance. The experimental design, using a pre-test/post-test system with two groups, was employed. The study population consisted of 40 third-grade students from Al-Mahawil Primary School for Boys during the 2024 academic year. The sample was selected randomly. Key recommendations included focusing on developing motor coordination and 100-meter sprint performance among third-grade students; incorporating recreational exercises and small games to develop motor coordination in conjunction with the development of basic 100-meter sprint skills; and ensuring safety measures and age-appropriate equipment with clear instructions. The instructions and explanation of the exercise were detailed and presented correctly. The use of small, purposeful, and fun recreational games had a direct and significant impact on the children's performance, leading to improved motor skills. Significant differences were found between the pre-test and post-test, favoring the post-test and the experimental group. All the motor exercises under investigation, as well as overall performance, improved, positively affecting all research variables for third-grade students. Recreational exercises had a positive effect on developing neuro-motor coordination and 100-meter sprint performance in both the experimental and control groups of third-grade students. The experimental group demonstrated superior development in neuro-motor coordination and 100-meter sprint performance among third-grade students.
Keywords: Recreational physical exercises; neuromotor coordination; 100m sprint